2021
DOI: 10.1097/brs.0000000000004113
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of the Cervical Disc Prosthesis

Abstract: Study Design. Retrospective analysis was performed on data from 251 patients that were included in two randomized, double-blinded clinical trials comparing clinical results of anterior cervical discectomy and arthroplasty (ACDA) to anterior cervical discectomy and fusion (ACDF), and anterior cervical discectomy (ACD), for single-level disc herniation.Objective. This study aimed to investigate whether the ACDA procedure offers superior clinical results 2 years after surgery, to either ACDF or ACD without instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Most surgeons, however, perform Anterior Cervical Discectomy with Fusion (ACDF) to maintain disc height and cervical alignment and promote bony fusion to prevent instability [1]. Although there has been some debate on the necessity of interbody fusion, recent studies have shown that patients treated with ACD alone fare worse [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Most surgeons, however, perform Anterior Cervical Discectomy with Fusion (ACDF) to maintain disc height and cervical alignment and promote bony fusion to prevent instability [1]. Although there has been some debate on the necessity of interbody fusion, recent studies have shown that patients treated with ACD alone fare worse [2][3][4].…”
Section: Introductionmentioning
confidence: 99%